Translation and adaptation of the German version of the Veterans Rand—36/12 Item Health Survey - Buchholz, Ines; Feng, You-Shan; Buchholz, Maresa; Kazis, Lewis E.; Kohlmann, Thomas (Health and quality of life outcomes, 2021)
Background The translated and culturally adapted German version of the Veterans Rand 36 Items Health Survey (VR-36), and its short form, the VR-12 counterpart, were validated in a German sample of orthopedic (n = 399) and psychosomatic (n = 292) inpatient rehabilitation patients. Methods The instruments were analyzed regarding their acceptance, distributional properties, validity, responsiveness and ability to discriminate between groups by age, sex and clinically specific groups. Eligible study participants completed the VR-36 (n = 169) and the VR-12 (n = 177). They also completed validated patient-reported outcome measures (PROs) including the Euroqol-5 Dimensions 5 Level (EQ-5D-5L); Depression, Anxiety and Stress Scale (DASS); Hannover Functional Abilities Questionnaire (HFAQ); and CDC Healthy Days. The VR-12 and the VR-36 were compared to the reference instruments MOS Short Form-12 Items Health Survey (SF-12) version 1.0 and MOS Short Form-36 Items Health Survey (SF-36) version 1.0, using percent of completed items, distributional properties, correlation patterns, distribution measures of known groups validity, and effect size measures. Results Item non-response varied between 1.8%/1.1% (SF VR-36 /RE SF-36 ) and 6.5%/8.6% (GH VR-36 /GH SF-36 ). PCS was normally distributed (Kolmogorov–Smirnov tests: p > 0.05) with means, standard deviations and ranges very similar between SF-36 (37.5 ± 11.7 [13.8–66.1]) and VR-36 (38.5 ± 10.1 [11.7–67.8]), SF-12 (36.9 ± 10.9 [15.5–61.6]) and VR-12 (36.2 ± 11.5 [12.7–59.3]). MCS was not normally distributed with slightly differing means and ranges between the instruments (MCS VR-36 : 36.2 ± 14.2 [12.9–66.6], MCS SF-36 : 39.0 ± 15.6 [2.0–73.2], MCS VR-12 : 37.2 ± 13.8 [8.4–70.2], MCS SF-12 : 39.0 ± 12.3 [17.6–65.4]). Construct validity was established by comparing correlation patterns of the MCS VR and PCS VR with measures of physical and mental health. For both PCS VR and MCS VR there were moderate (≥ 0.3) to high (≥ 0.5) correlations with convergent (PCS VR : 0.55–0.76, MCS VR : 0.60–0.78) and small correlations (< 0.1) with divergent (PCS VR : < 0.12, MCS VR : < 0.16) self-report measures. Known-groups validity was demonstrated for both VR-12 and VR-36 (MCS and PCS) via comparisons of distribution parameters with significant higher mean PCS and MCS scores in both VR instruments found in younger patients with fewer sick days in the last year and a shorter duration of rehabilitation. Conclusions The psychometric analysis confirmed that the German VR is a valid and reliable instrument for use in orthopedic and psychosomatic rehabilitation. Yet further research is needed to evaluate its usefulness in other populations.